Biophysical Properties and Cytotoxicity of Feruloylated Helix Lucorum Hemocyanin - Maya Guncheva (Acta Chimica Slovenica, 2020)
For the first time Helix lucorum hemocyanin (HlH) has been feruloylated. Two HlH conjugates with 40- and 120- ferulic acid residues were prepared, denoted as FA-HlH-1 and FA-HlH-2. Expectedly, the feruloylation of HlH induced a rearrangement of the protein molecule, a decrease in the α-helical structure at the expense of β-structures was observed. Besides, the FA-HlH conjugates were more prone to aggregation, which is probably due to the stabilization of the partially unfolded protein molecules by non-covalent bonding. Interestingly, the thermal stability of HlH was not affected by the modification. The native and feruloylated HlH were not toxic to normal fibroblasts (BJ cells). We observed a decrease in cell viability of breast cancer MCF-7 cells to about 66% after a 48h exposure to 70 µg/well of FA-HlH-2.